2456. Stenotrophomonas maltophilia (SM) Pseudo-outbreak Associated with Bronchoscope - Eichenblat, Siobhan (Open Forum Infect Dis, 2019)
BACKGROUND: Stenotrophomonas maltophilia (SM) is a multi-drug-resistant Gram-negative organism that typically impacts patients with long hospital stays or severe immunocompromise. In Q4 2017, an increase in rates of SM from adult bronchoscopic alveolar lavage (BAL) specimens was detected. METHODS: The charts of all patients with SM from BAL specimens during the time frame in question were reviewed for commonalities, clinical symptoms and antibiotic treatment for Stenotrophomonas. Incidence rate ratios for the 21 months prior to, 3 months during and 15 months after the increase were compared using Fisher exact test. RESULTS: Quarter 4 2017 rates of SM isolated from BALs performed in patients >/ = 18 years of age increased significantly from baseline of 0.46 to 2.22 per 10,000 patient-days. Upon chart review 75% (12/16) of patients with SM during the increase had BALs performed with a specific bronchoscope. Q4 2017, 22 patients had a BAL performed with the scope in question with 16 sent for culture. 75% (12/16) of the BALs done with this scope during Q4 2017 grew SM. The scope was pulled from use once the association was identified. ATP and high-level disinfection records were reviewed with no failures noted. The scope was sent to an independent lab where boroscope evaluation showed epoxy lifting. Cultures from the scope were unrevealing. After the scope was removed from service, rates of SM from adult BALs dropped significantly back to 0.58 per 10,000 patient-days (Figure 1). Upon clinical review, SM was deemed clinically insignificant in all but 1 case, however, 8 of the 12 patients received antibiotic treatment for this pathogen. To date, none of the patients in question had subsequent cultures with SM. No adverse events due to antibiotic therapy have been noted 10 of the patient isolates were retrieved and sent for pulsed-field gel electrophoresis testing. All came back with identical PFGE patterns strongly suggesting a point source. CONCLUSION: While the bronchoscope culture did not grow SM, the identical PFGE patterns in patients without evidence of active infection suggested a point source. Return of SM rates to baseline following removal of the scope from service strongly suggest a pseudo-outbreak resulting from a reusable bronchoscope. [Image: see text] DISCLOSURES: All authors: No reported disclosures.